1993
DOI: 10.1111/j.1365-2621.1993.tb06098.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Mozzarella Cheese Filled with Dairy, Egg, Soy Proteins, and Gelatin

Abstract: The Rheological behavior of mozzarella cheese filled with various proteins (whey protein, caseinate, egg white, soy protein isolate, gelatin) incorporated was determined by uniaxial compression at 10°C and the effect of temperature (lOT--6OT) by dynamic measurement. Mozzarella cheese with whey protein, caseinate, egg white, and soy protein isolate showed significant water retention during heating. Among the proteins, soy protein isolate induced the strongest gel network structure with mozzarella cheese. All pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
5
23
0
2
Order By: Relevance
“…A decrease in both G' and G" with increasing temfor the G" results. perature was also reported by Hsieh et al (1993) on Mozzarella…”
Section: Dynamic Viscoelastic Measurementssupporting
confidence: 70%
“…A decrease in both G' and G" with increasing temfor the G" results. perature was also reported by Hsieh et al (1993) on Mozzarella…”
Section: Dynamic Viscoelastic Measurementssupporting
confidence: 70%
“…[36] Similar responses have been reported by other researchers, including melted cheese. [8,12,13,37] We found that both G′ and G″ decreased with increasing temperature due to thermal softening. But G′ decreased at a faster rate than G″, and the change was more pronounced for a regular-fat process cheese at a temperature of 50°C and lower frequencies.…”
Section: Frequency Sweep Test (Dynamic Viscoelastic Properties)mentioning
confidence: 92%
“…Diefes et al [12] performed dynamic tests to compare rheological properties of low-moisture, part-skim Mozzarella cheese subjected to freezing storage and refrigerated storage. Hsieh et al [13] used dynamic tests to evaluate effect of temperature on the functional properties of Mozzarella cheese containing various protein fillers. Venugopal and Muthukumarappan [14] studied the dynamic rheological properties of Cheddar cheese during heating and cooling (25°C to 60°C and back) with different fat and moisture levels for up to 24 weeks of aging.…”
Section: Introductionmentioning
confidence: 99%
“…Fat has been replaced with other ingredients in making low fat cheeses. Mozzarella cheese containing soy protein produced strong gel networks as indicated by highest compressive stress, showing that soy protein functioned like an increase in casein rather than a decrease in fat (Hsieh et al, 1993). Though egg, whey and caseinate significantly influenced the magnitude of G and G , they showed no effect on compressive stress.…”
Section: Uniaxial Compressionmentioning
confidence: 81%